KNOWLEDGE, REATIONALITY AND SYMBOLIC: ARISTOTLE AND CASSIRER, DISTINCT INTERPRETATIONS ABOUT THE HUMAN KNOWLEDGE AND ITS POSSIBLE REFLECTIONS ON GEOGRAPHICAL EPISTEMOLOGY - Pereira, Clevisson Junior (2014)
From two Theories of Knowledge, based in Aristotle (Posterior Analytics) and Ernst Cassirer (An essay on man), this text explore the notions of scientific knowledge and symbolic knowledge, respectively. With these notions, and with its inherent philosophies, the present work will ponder how these theorizations have influenced/influences in geographical epistemology.